2005
DOI: 10.1139/g04-081
|View full text |Cite
|
Sign up to set email alerts
|

The genomic composition of Tricepiro, a synthetic forage crop

Abstract: Chromosome in situ hybridization (FISH and GISH) is a powerful tool for determining the chromosomal location of specific sequences and for analysing genome organization and evolution. Tricepiro (2n = 6x = 42) is a synthetic cereal obtained by G. Covas in Argentina (1972), which crosses hexaploid triticale (2n = 6x = 42) and octoploid Trigopiro (2n = 8x = 56). Several years of breeding produced a forage crop with valuable characteristics from Secale, Triticum, and Thinopyrum. The aim of this work is to analyse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Arrows show 16 chromosomes with hybridization signals; four of them were identified as pairs 2 and 4 of the D genome. Bars = 5 lm Taking into account the pSc119.2 pattern of signal distribution described by different authors (BrasileiroVidal et al 2005;Ferrari et al 2005;Molnár et al 2009;Mukai et al 1993;Sepsi et al 2008) in SH16 INTA 14 chromosomes of the B wheat genome and the 4A pair of the A wheat genome have been identified. The remaining hybridized chromosomes appear to belong to the A and/or D genomes of wheat and to the Thinopyrum genome.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Arrows show 16 chromosomes with hybridization signals; four of them were identified as pairs 2 and 4 of the D genome. Bars = 5 lm Taking into account the pSc119.2 pattern of signal distribution described by different authors (BrasileiroVidal et al 2005;Ferrari et al 2005;Molnár et al 2009;Mukai et al 1993;Sepsi et al 2008) in SH16 INTA 14 chromosomes of the B wheat genome and the 4A pair of the A wheat genome have been identified. The remaining hybridized chromosomes appear to belong to the A and/or D genomes of wheat and to the Thinopyrum genome.…”
Section: Discussionmentioning
confidence: 98%
“…In situ hybridization techniques (GISH, genomic in situ hybridization, and FISH, fluorescent in situ hybridization) were performed on mitotic cells according to Ferrari et al (2005). Slide preparations were incubated in DNAse-free RNAse (100 lg/ml) in 2 9 SSC for 1 h at 37°C in a humid chamber and washed three times in 2 9 SSC at room temperature for 5 min.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that rapid genome changes occur following F 1 or allopolyploid formation: 1) the non-random elimination of coding and non-coding DNA sequences; 2) epigenetic changes, such as DNA methylation of coding and non-coding DNA, leading, among other things, to gene silencing; 3) the activation of genes and retro-elements, which, in turn, alters the expression of adjacent genes (Feldman and Levy, 2005); and 4) chromosome reorganization, with the gain or loss of chromosomes or whole genomes (Bernardo et al , 1988; Soler et al , 1990; Soltis and Soltis, 2000; Ferrari et al , 2005). An example of a particular case of the harmonic coexistence of several genomes achieved by chromosomal rearrangement and gain or loss of chromosomes or even completed genomes, was observed in the tricepiro Don René INTA (Ferrari et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…An example of a particular case of the harmonic coexistence of several genomes achieved by chromosomal rearrangement and gain or loss of chromosomes or even completed genomes, was observed in the tricepiro Don René INTA (Ferrari et al , 2005). This cultivar was obtained by crossing a hexaploid triticale (2n = 42, AABBRR, A, B from wheat and R from rye) with an octoploid trigopiro (2n = 8x = 56, AABBDDJJ, with A, B, D from wheat and J from wheatgrass), and became stable at 2n = 42 .…”
Section: Introductionmentioning
confidence: 99%